Weak Labour, Strong Interests: Polish Trade Unions and the Integration of EU Energy and Service Markets. (8th December 2016) - Bernaciak, Magdalena; Lis, Aleksandra
Abstract: This paper examines the motives behind the EU‐level activism of CEE trade unions, which are commonly regarded as weak actors. To this end, it studies lobbying and protest actions staged by Polish labour organizations in relation to proposals for the EU Emission Trading Scheme Directive and the EU Services Directive. The analysis confirms the salience of interest‐based accounts of supranational union action, but it also shows that labour interests are context‐specific, influenced by economic conditions and regulatory changes in particular market segments. In this regard, priority given by the unions to job preservation or the improvement of social standards has important implications for their positions; it also determines the selection of their allies at national and transnational levels.